NILAI PENDIDIKAN PADA SURAH AL-ALAQ AYAT 1-5 MENURUT QURAISH SHIHAB - Lubis, Sakban; Nasution, Muhammad Roihan (Jurnal Ilmiah Al-Hadi, 2018)
Quraish Shihab is also known as a reliable writer and speaker. Based on a solid scientific background that he traveled through formal education and supported by his ability to express opinions and ideas in simple language, but straightforward, rational, and moderate thinking tendencies, he appeared as a lecturer and writer that can be accepted by all levels of society. He conducted these lectures in a number of prestigiousmosques in Jakarta, such as the Masjid al-Tin and Fathullah, in government officials such as the Istiqlal study and in a number of television or electronic media stations, especially in the month of Ramadan. Some television stations, such as RCTI and Metro TV have special programs during Ramadan that are nurtured by him. M. Quraish Shihab stressed the need to comprehend Divine revelation contextually and not merely fixated on the textual meaning so that the messages contained in it could be functioned in real life. He also motivated many of his students, especially at the postgraduate level, to be brave in interpreting the Koran, but by sticking tightly to the rules of interpretation that had been considered standard.